2013
DOI: 10.1007/s00277-013-1910-2
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1/2 study of oral panobinostat combined with melphalan for patients with relapsed or refractory multiple myeloma

Abstract: Panobinostat is a histone deacetylase inhibitor that has shown synergistic preclinical anti-myeloma activity when combined with other agents, recently exhibiting synergy with the alkylating agent melphalan (Sanchez et al., Leuk Res 35(3):373-379, 2011). This phase 1/2 trial investigated the safety and efficacy of panobinostat in combination with melphalan for relapsed/refractory multiple myeloma patients. There were four different trial treatment schedules due to tolerability issues, with the final treatment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…However, toxicity has been a concern in the clinical settings. For example, the serious hematological toxicity observed with the combination of panobinostat and melphalan in MM precluded the demonstration of clinical activity in this particular clinical trial [21]. In our ex vivo experiments, we observed a therapeutic window for plasma cells as compared with lymphocytes, which is further confirmed in in vivo studies, in which we showed the clear efficacy of the compound with an acceptable toxicity.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, toxicity has been a concern in the clinical settings. For example, the serious hematological toxicity observed with the combination of panobinostat and melphalan in MM precluded the demonstration of clinical activity in this particular clinical trial [21]. In our ex vivo experiments, we observed a therapeutic window for plasma cells as compared with lymphocytes, which is further confirmed in in vivo studies, in which we showed the clear efficacy of the compound with an acceptable toxicity.…”
Section: Discussionsupporting
confidence: 75%
“…Preclinical data have shown the synergy of panobinostat with melphalan [18] and that of entinostat with bendamustine [19]. Unfortunately, this effect has not been observed in the clinical setting, partly due to the hematological toxicity of these combinations [20, 21]. Our hypothesis is that this hybrid molecule may be able to overcome these caveats.…”
Section: Introductionmentioning
confidence: 99%
“…Other agents, including elotuzumab (anti-CS-1 antibody), anti-CD38 antibody, and panobinostat, which are newly available to treat MM might be effective for ALA [23][24][25][26].…”
Section: Discussionmentioning
confidence: 98%
“…Panobinostat was combined with oral melphalan in a Phase I/II trial of 40 RR MM patients [64]. The MTD was 20 mg of panobinostat (days 1, 3 and 5 of week 1 only for each 28-day cycle) and 0.05 mg/kg melphalan (days 1, 3 and 5 of each cycle).…”
Section: Phase II Trialsmentioning
confidence: 99%